Penyusunan Buku Panduan Manajemen Dakwah Lingkungan Berbasis Tafsir Ekologis Q.S. Al-Rum: 41 dan Aplikasinya dalam Gerakan Sedekah Sampah - Supeno Supeno; Moh. Agil Nuruzzaman; Nandipah Roa'zah; Muslimatun Diana Muazaroh; Diana Elfiyatul Afifah; Sukirno Sukirno; Munahar Munahar (Sciences du Nord Community Service, 2024)
Please use only the styles of this template (MS title, Authors, Affiliations, Correspondence, Normal for your text, and Headings 1–3). Figure 1 uses the style Caption. The abbreviation “Fig.” should be used when it appears in running text and should be followed by a number unless it comes at the beginning of a sentence, e.g.: “The results are depicted in Fig. 5. Figure 9 reveals that.” Figures and tables as well as their captions must be inserted in the main text near the location of the first mention (not appended to the end of the manuscript). Regarding colour schemes, it is important that your maps and charts allow readers with colour vision deficiencies to correctly interpret your findings. Please check your figures using the Coblis – Color Blindness Simulator and revise the colour schemes accordingly.